Penerapan Guidelines for the Development of Measures to Combat Counterfeit Drugs WHO 1999 di Indonesia - Bunga Lutfiana Sari; Ika Riswanti Putranti; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
The globalization era, which now has increasingly removed the interstate's barrier, is not solely positive. One of the negative impacts which has occurred is the inevitable dissemination of counterfeit drugs across the world. Thus, the counterfeit drugs issue has become a common problem of international society and has to be tackled together. The discourse on the issue and technical countermeasures are relentlessly sought by WHO along with its member countries until the creation of Guidelines for the Development of Measures to Combat Counterfeit Drugs (GDMCCD) in 1999. The guidelines were formulated for harmonizing member countries' efforts in the most systematic and effective way in tackling counterfeit drugs dissemination. In this thesis, Indonesia as one of the WHO member countries, abides and implements the guidelines. This thesis will discuss about the motives behind Indonesia's GDMCCD 1999 implementation into governmental system and municipal law while the guideline is merely a recommendation. Through the neoliberalism perspective, which is rich in the explanation about self-interest in international cooperation, this research provides explanatory analysis about Indonesia's interest in the guidelines implementation. The result of this research finds that Indonesia has distributed the vision and mission of GDMCCD into national regulations and Indonesia has interest-based motives. National interest (economic benefits, political supports, and information) and common interest (human security, transnational crime, and transaction cost) are the main motives of Indonesia in the implementation.